2010
DOI: 10.1103/physreve.81.046304
|View full text |Cite
|
Sign up to set email alerts
|

Phase relationship in laminar channel flow controlled by traveling-wave-like blowing or suction

Abstract: The phase relationship between the streamwise and the wall-normal velocity disturbances induced by a traveling-wave-like blowing or suction control [T. Min, J. Fluid Mech. 558, 309 (2006)] in a two-dimensional laminar Poiseuille flow is investigated. The investigation is done by solving the linearized Navier-Stokes equation and by using the identity equation between the skin-friction drag and the Reynolds shear stress [K. Fukagata, Phys. Fluids 14, L73 (2002)]. It has been known that a traveling wave creates a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
23
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 25 publications
7
23
1
Order By: Relevance
“…Their control succeeded to sustain a sublaminar drag both in laminar and turbulent flows: the negative RSS was induced in the region near the wall when the wave travels to the upstream direction. Mamori, Fukagata, & Hoepffner (2010) reproduced Min et al 's laminar flow results and revealed by means of a linear analysis and a detailed phase analysis the mechanism to induce this negative RSS. The viscosity induces the phase lead of the streamwise velocity fluctuation from the wall-normal velocity fluctuation and the non-quadrature between them induced thereby makes the RSS negative.…”
Section: Introductionsupporting
confidence: 49%
See 2 more Smart Citations
“…Their control succeeded to sustain a sublaminar drag both in laminar and turbulent flows: the negative RSS was induced in the region near the wall when the wave travels to the upstream direction. Mamori, Fukagata, & Hoepffner (2010) reproduced Min et al 's laminar flow results and revealed by means of a linear analysis and a detailed phase analysis the mechanism to induce this negative RSS. The viscosity induces the phase lead of the streamwise velocity fluctuation from the wall-normal velocity fluctuation and the non-quadrature between them induced thereby makes the RSS negative.…”
Section: Introductionsupporting
confidence: 49%
“…According to the phase analysis by Mamori, Fukagata, & Hoepffner (2010), the RSS in a laminar flow is generated by the non-quadrature between the streamwise and wall-normal velocities fluctuations. The Fourier transform is defined as…”
Section: Wall-normal Lorenz Forcementioning
confidence: 99%
See 1 more Smart Citation
“…The positive and negative ⟨− u v⟩ alternate while the non-quadrature between u and v appears in the region near the wall. A significant amount of ⟨− v θ⟩ also appears in the region near the wall, which creates the periodic contribution to the heat transfer similarly to that to the friction drag (Min et al, 2006;Mamori et al, 2010). The upstream wave-like wall deformation or blowing and suction is known to work to destabilize the flow as was shown by DNS (Min et al, 2006;Nakanishi et al, 2012).…”
Section: Contributions To Drag and Heat Transfermentioning
confidence: 76%
“…Fig. 4 shows a typical time-fluid volume curve for the left ventricle of a human heart [1]: it's easy to observe that there are discontinuities in transition from suction phase to sending phase and therefore it cannot be set directly to linear motor [29][30][31][32]. It was necessary to interpolate it through fourth order polynomials.…”
Section: Testbenchmentioning
confidence: 99%